Indigenous Symbolic Visual Communication Design (ISVCD) Framework: Sustaining Indigenous Knowledge Through A Systematic Innovation Approach. - Chu Hiang, Goh (UNIMAS, 2025)
This research addresses the critical need to preserve and transmit Indigenous symbolic communication in the digital age by formalising a culturally grounded visual communication framework that employs a multidisciplinary approach and hybrid model. Rooted in the Indigenous Research Paradigm, the study aims to: (1) formulate a design framework for Indigenous symbolic visual communication, (2) implement the framework through a case study involving the Tatandu visual language, and (3) develop and apply validation strategies to assess the framework’s effectiveness in symbol representation and Indigenous value preservation. The research presents the Indigenous Symbolic Visual Communication Design (ISVCD) Framework, a multilayered model combining a hybrid visual communication and semiotic framework, the TRIZ Law of System Completeness, and Indigenous epistemologies. An Indigenous Symbolic Design Mapping (ISDM) Instrument was developed to operationalise the framework and guide symbol analysis and co-design. A case study involving local Indigenous experts and youth participants from the Murut Tahol community in Sabah. Facilitated the extraction, interpretation, and digital redesign of 14 Indigenous symbols called Tatandu, each associated with their Indigenous core values. Validation was conducted using a triangulation strategy: (1) expert review of symbol accuracy and inventory integrity, (2) empirical testing of the ISDM Instrument using confusion matrix analysis, and (3) thematic comparison of core values between traditional and digital symbols. The results confirm that the ISVCD Framework maintains both symbolic meaning and cultural authenticity across digital transformation processes. The findings affirm the central hypothesis that “visual communication can be formalised in a design framework and successfully applied to Indigenous symbolic communication language”. This research contributes a scalable, epistemologically aligned model for Indigenous digital expression, an innovative approach using TRIZ methodology as a social-technical system with implications for Indigenous symbol preservation, design principles, and inclusive visual media development.